Thiamine combined with vitamin C in sepsis or septic shock: a systematic review and meta-analysis. (June 2021) - Ge, Zengzheng; Huang, Jiewu; Liu, Yawei; Xiang, Jun; Gao, Yanxia; Walline, Joseph Harold; Lu, Xin; Yu, Shiyuan; Zhao, Lina; Li, Yi
Abstract : Background: Thiamine and vitamin C have been increasingly used in patients with sepsis or septic shock because of their potential for improving metabolism and reducing mortality. Objective: We aim to determine if thiamine combined vitamin C can reduce mortality in patients with sepsis or septic shock. Evidence sources and study selection: We comprehensively searched the PubMed, Embase, Cochrane Library, and Web of Science databases from their inception dates through 1 January 2021. Literature works evaluating the efficacy of thiamine combined vitamin C in patients with sepsis or septic shock were considered. Data extraction and outcome measurements: Two reviewers extracted data and assessed study quality. A meta-analysis was performed to calculate an odds ratio (OR), 95% confidence intervals (CIs), and P values for in-hospital mortality (primary outcome). Secondary outcomes included duration of ICU stay, duration of hospital stay, duration of vasopressor use, and change in sequential organ failure assessment (SOFA) scores. Results: Seven randomized controlled trials were identified, encompassing a total of 868 patients. There was no statistical difference between groups for in-hospital mortality (OR: 1.11; 95% CI [0.79–1.56]; P = 0.55). Other than improving SOFA score during the first 72 h after enrollment and duration of vasopressor use, we found no other significant associations. Conclusions: Despite widespread enthusiasm for thiamine combined with vitamin C for sepsis and septic shock, we only found an association with reduced SOFA score and time of vasopressor use. There was no association with in-hospital mortality.